The Moderating Role of Corporate Governance on The Relationship of Capital Structure on Firm Value - An-Nabilah, A. Khumairoh; Zulfatillah, Auliya (AKUNSIKA: Jurnal Akuntansi dan Keuangan, 2025)
The development of the business world at this time has led to intense competition, which requires companies to continue to increase their value because company value is one of the goals that determine the long-term success of the company. This study aims to examine the effect of capital structure on firm value and to examine the moderating effect of corporate governance on the effect of capital structure on firm value. This research is quantitative research using secondary data taken from the official website of the Indonesia Stock Exchange (IDX) and the official website of each company. The population in this study are food and beverage companies listed on the IDX in 2019-2023. The sample in this study consisted of 230 companies selected based on purposive sampling technique with criteria that have consistently reported annual reports in 2019-2023. The data analysis technique used in this study is moderation regression analysis using SPSS version 25. The results showed that capital structure negatively affects firm value and corporate governance is able to moderate the effect of capital structure on firm value.